Searches for new physics that couple with third generation fermions - Valeria D'Amante, on behalf of the CMS collaboration (SciPost Physics Proceedings)
The $τ$ lepton, with a mass of $1776.86 ± 0.12$ MeV, is unique in its ability to decay into hadrons and a neutrino. Approximately one-third of $τ$ decays produce an electron or a muon and two neutrinos, denoted as $τ_e$ and $τ_μ$. The remaining decays, mainly involving hadrons and a tau neutrino, are denoted as $τ_h$. At the CERN LHC, searches involving $τ$ leptons are crucial for studying the decay of Higgs bosons to $τ$ pairs, probing Yukawa couplings, and CP properties of the Higgs. These measurements support Standard Model (SM) tests and searches for Beyond Standard Model (BSM) physics, including new or heavy Higgs bosons, leptoquarks, supersymmetric particles, or gauge bosons. The $τ$ lepton polarization in Z boson decays is also significant for probing the SM. Despite its potential as a portal to new physics, the $τ$ lepton's decay products, especially neutrinos and hadrons, make its reconstruction and identification challenging at the LHC. At the CMS experiment, neutrinos contribute to Missing Transverse Energy (MET), and hadronically decaying $τ$ leptons are often misidentified as jets, complicating the separation of $τ$-involved processes from background processes.